1982
DOI: 10.1029/jb087ib07p05593
|View full text |Cite
|
Sign up to set email alerts
|

Galapagos Hot Spot‐Spreading Center System: 1. Spatial petrological and geochemical variations (83°W–101°W)

Abstract: We report on the petrology and geochemistry of basalts dredged at 40–50 km intervals along the Galapagos Spreading Center, between 83°W and 101°W (40 stations). Emphasis is on spatial variations of ‘whole rock’ major elements, rare earths, trace metals of the first transition series, and the nature of phenocryst assemblages and their abundances. These results provide new constraints on the nature and scale of mantle source heterogeneities, melting conditions, thermal field, and dynamics of crustal formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
169
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(180 citation statements)
references
References 51 publications
11
169
0
Order By: Relevance
“…It is also clear that different hot spots (e.g., Iceland and the Azores lead to distinct major element effects on MORB. This latter point has been emphasized previously by Langmuir and Hanson [1980] and Schilling et al [1982].…”
Section: Galapagos Spreading Centermentioning
confidence: 53%
See 1 more Smart Citation
“…It is also clear that different hot spots (e.g., Iceland and the Azores lead to distinct major element effects on MORB. This latter point has been emphasized previously by Langmuir and Hanson [1980] and Schilling et al [1982].…”
Section: Galapagos Spreading Centermentioning
confidence: 53%
“…Corrections were applied to all analyses determined at the Smithsonian Institution [Melson et al, 1977] or that were reported to be consistent with the Smithsonian data [i.e., Schilling et al, 1985], based on the factors reported in KL89 (their Figure 5), so that all data are consistent with those determined at Lamont and by wet chemistry at Atlantic and Pacific MORB. These subtle inter-ocean differences contribute to the observed "width" of the global correlations for normal ridges of Figure 15.…”
Section: 1mentioning
confidence: 99%
“…Variation in basalt composition is not isolated to the SWIR [Melson et al, 1976], and although MORB is dominated by incompatible element depleted tholeiite, the occurrence of incompatible element enriched basalt (E-MORB) reflects a key component of ocean crust generation. In some cases E-MORB is attributed to nearby plume-influence, for example the Iceland plume on the northern MidAtlantic Ridge [Bougault et al, 1988; or Galapagos plume on the Galapagos Spreading Center [Christie and Sinton, 1981;Fisk et al, 1982;Schilling et al, 1976;Schilling et al, 1982]. However, for non-plume influenced ridge sections, most notably along the East Pacific Rise (EPR) [Batiza and Niu, 1992;Langmuir et al, 1986;Mahoney et al, 1994;, the occurrence is not well understood.…”
Section: Introductionmentioning
confidence: 98%
“…7). On the largest scale, isotopic and incompatible trace element ratios reveal a westerly decrease in source enrichment with distance from the Galapagos hotspot that correlates with decreasing crustal thickness and increasing axial depth, MBA and (where investigated) melt sill depth (Schilling et al 1982;Detrick et al 2002;Sinton et al 2003) This overall geochemical trend is subdivided into three .200 km-long geochemical provinces reflecting changes in source enrichment ('primary magmatic segments' of Sinton et al 1991): an enriched-mid-ocean ridge basalt (E-MORB) province east of 92840 ′ W; a transitional (T-MORB) province between the 92840 ′ W third-order offset and the 95830 ′ W PR tip; and a normal (N-MORB) province west of 95830 ′ W (Fig. 7b, c, Sinton et al 2003;Cushman et al 2004;Ingle et al 2010).…”
Section: Geochemical Properties Of Discontinuities and Ridge Segmentsmentioning
confidence: 99%
“…Along many intermediate spreading ridges, regional gradients in ridge properties are observed that extend over hundreds to thousands of kilometres and are attributed to gradual variations in magma supply with proximity to local hotspots (e.g. the Galapagos hotspot near the GSC; Schilling et al 1982) or coldspots such as AAD along the SEIR (Klein et al 1991;West et al 1994;Christie et al 1998). In addition to these regional gradients, 'tectonic corridors' have been identified from systematic differences in the rate and asymmetry of across-axis seafloor subsidence with age that span multiple TF-bounded segments (Hayes & Kane 1994).…”
Section: Intermediate Spreading Ridgesmentioning
confidence: 99%